Pengaruh Likuiditas, Pertumbuhan Penjualan, Ukuran Perusahaan, dan Perputaran Modal Kerja terhadap Earning Per Share Perusahaan Sub Sektor Retail Trade yang Terdaftar di BEI Tahun 2014–2018 - Nengah Devi Yuliantini; Ni Luh Gede Erni Sulindawati (Jurnal Ilmiah Akuntansi dan Humanika, 2021)
The purpose of this study is to find out how the financial aspects of earnings per share of the Retail Trade sub-sector companies on the Stock Exchange in 2014 - 2018. This study applies a purposive sampling technique to draw research samples, the provisions of Retail Trade companies listed on the Stock Exchange, Retail Trade companies where total assets above 100 billion at the end of 2018 and Retail Trade companies that have an average negative earnings per share trend in 2014 - 2018. From 20 Retail Trade companies, a sample of 7 companies is obtained with annual consideration. Secondary data is data from this study in the form of financial reports that are accessed and downloaded through the IDX official website and the SPSS 16.0 for Windows program that is used to process this study data. Through the analysis carried out, the results show that liquidity, sales growth, company size, and working capital turnover have a significant positive effect on earnings per share of Retail Trade companies affecting earnings per share.